QoS-based Self-Management for Business Processes - Comes, Diana; Zapf, Michael; Geihs, Kurt (Electronic Communications of the EASST, 2010)
Business processes are commonly implemented as compositions of Web Services, using the Business Process Execution Language (BPEL) as an orchestration speciﬁcation. Business processes do not only require an appropriate setup but also need to be monitored throughout their runtime, especially when Quality-of-service (QoS) constraints have to be met. Monitoring results may be used for the automated reconﬁguration and optimization of business processes. We show how we achieve self-management based on QoS constraints within our system. The BPRules Language that we set up can be used to improve the QoS behavior of business processes by triggering appropriate management actions on the process. Also we propose a service selection strategy for the dynamic selection and replacement of services within business processes.